Belt conveying of minerals - Yardley, E. D. (Woodhead Publishing series in metals and surface engineering., 2008)
Belt Conveying of Minerals is a comprehensive reference on the science and technology of belt conveyors, aimed at providing mine and quarry operators, as well as engineering students, with a balanced view of the technical issues associated with belt conveyors and to assist in the decision-making process when installing belt conveyor systems. A discussion of the history and economics of conveyor applications sets the scene. Conveyor design is investigated in detail, covering power requirements, belt tensioning, and hardware. Principles regarding construction and joining of belts are outlined and a helpful and practical overview of relevant standards, belt test methods, and issues surrounding standardisation is given. Conveyor belt systems can represent a significant operational hazard, so the authors have set out to highlight the important area of safety, with consideration given to fire/electrical resistance, as well as the interface between personnel and conveyor systems - including nip points and operational issues such as man-riding. Selected case studies illustrate some practical aspects of installation and operation. A comprehensive reference on the science and technology of belt conveyorsProvides a balanced view of the technical issues associated with belt conveyorsInvestigates conveyor design and outlines the principles of construction.